Pengenalan Teknologi Robotika Berbasis IoT pada Siswa SMKN 5 Majene - Purnamawati Purnamawati; Muhammad Akil; Nuridayanti Nuridayanti; Usman Mulbar; Hasanah Nur (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
The development of robotics technology has now spread to various sectors, one of which is the world of education. Robots in the world of education are used to make it easier for teachers to provide interactive and in-depth learning for students. This PKM activity indirectly helps the government in improving the quality and competence of students and teachers in vocational schools/high schools, which so far is in accordance with the central government program, namely intensively carrying out vocational/high school revitalization activities to improve the quality and competitiveness of human resources. This PKM activity was carried out at SMKN 5 Majene. This activity is planned to last for 8 (eight) months with a schedule of activities starting from preparing proposals, implementing activities in schools, and reporting to LP2M UNM. The training activity was carried out by providing 2 materials, namely the first material: introduction to robots and their important parts, Internet of Things (IoT), programming based on Arduino IDE, how to install and configure Android applications, and robot operation. The second material is a practical test of controlling an IoT-based robot using an Android application. In this second material, the training participants will try to control the robot based on desired navigation, both forward, backward, turning left and turning right. Activities receive special attention for teachers and students because the material presented supports the technological development of the Industrial Revolution 4.0 and is very important for students as a provision to support their skills.